Prevalence of Occlusive Myocardial Infarction (OMI) in patients diagnosed with Non-ST-Elevation Myocardial Infarction (NSTEMI) at a single private facility in Cape Town, South Africa, during 2019 - Schoeman, Elmari (Division of Emergency Medicine, 2026)
Background: ST-Elevation Myocardial Infarction (STEMI) is strongly associated with acute coronary occlusion, leading to less urgent management of Non-ST-Elevation Myocardial Infarction (NSTEMI), often perceived as partial occlusion. However, 25.5% of NSTEMIs involve total coronary occlusion, significantly impacting mortality and Major Adverse Cardiovascular Events (MACE).1 The Occlusive Myocardial Infarction (OMI) vs Non-occlusive Myocardial Infarction (NOMI) paradigm has been proposed for better identification of acute myocardial infarction (AMI).2–5 Objectives: This study investigates the prevalence of OMI among NSTEMI patients in a private Cape Town emergency centre in 2019, analysing descriptive data, serial cardiac troponin I (cTnI) results, the proportion undergoing angiography, Thrombolysis in Myocardial Infarction (TIMI) flow grades, and door-to-angiogram times. Methods: A cross-sectional, observational study was conducted using a retrospective chart review of NSTEMI patients who underwent angiography. Data were analysed using descriptive statistics, Chi-square, and Mann-Whitney U-tests. Results: Among 31 NSTEMI patients, 83.9% (n=26) had OMI (median age 65 years, IQR 25), and 88.5% were male (p<0.001). Significant second cTnI levels (median 1450 ng/L, p=0.001) and a median door-to-angiogram time of 34 hours (IQR 48) were noted. The left anterior descending artery (34.6%) was the most common culprit lesion. Conclusion: The high prevalence of OMI among NSTEMIs highlights the limitations of the current STEMI/NSTEMI classification. Improved diagnostics and timely interventions, including emergent angiography and alternative treatments like thrombolysis, could enhance patient outcomes with reduced healthcare costs in resource-limited settings. The observed disparities and challenges in meeting international guidelines for timely interventions underscore the urgency of addressing accessibility issues. Heightened mortality and MACE risk among NSTEMIs with missed coronary occlusions1,7 highlight the need for expanded research to understand OMI prevalence and implications in South Africa.